1985: Community Issues, 1984-1986 - Houseal, Willie H. (Valdosta State University Archives and Special Collections, 1984)
Willie Houseal Scrapbook, Newspaper clippings, 1984-1986. Topics include: Victim-Witness Program, Betty Bechtel, RIF, Reading Is Fundamental, Zoning, Black Churches, Southside, Willie Houseal, Political Forum, City Council Election- 1985-1986, and Voting.
1 electronic document, PDF, 41 scanned images.
Keywords: Valdosta (Ga.); Lowndes County (Ga.); Newspapers; Scrapbooks; Voting; City council members; Elections